Why a Data Disclosure Law Is (Likely) Unconstitutional - Fiest, Max (The Columbia Journal of Law & the Arts, 2020)
Social media platforms have changed the very structure of communication. These platforms exert significant influence over how we get our news, how we form and join political movements, and how we connect with friends and family. But social media platforms are black boxes. Moderation algorithms are opaque–even to the platforms themselves—and attempts by third parties to research these algorithms are often frustrated. Because platforms withhold data necessary for public interest research, Congress might step in and mandate data access for certain researchers and journalists. I conclude that any such effort would (likely) be unconstitutional under the First Amendment. My purpose in this Note is twofold. First, I provide a framework for evaluating the constitutionality of a data disclosure law and explain which arguments are most likely to succeed. I also provide some analytical categories of platform data. These categories should help practitioners and policymakers evaluate the ways data disclosure might chill the free expression of platform users. Second, I explore how easily the First Amendment can be used to strike down economic regulations. Using a data disclosure law as an exhibit, I hope to illustrate and explain the Supreme Court’s shifting understanding of free speech. My Note proceeds in four parts. Part I provides relevant background and outlines a hypothetical data disclosure law; Part II explores the many arguments regulated platforms could deploy to invalidate a data disclosure law; Part III provides a brief recommendation to legislators seeking to draft a data disclosure law; and I conclude in Part IV by arguing for a reinterpretation of free speech jurisprudence.